Praktik Guru Sekolah Minggu Dalam Mengajarkan Karakter Kristiani Pada Anak – Anak di Gereja Kota Blitar - Cherish, Lidya; Sri Sadewo, Fransiscus Xaverius (Paradigma, 2025)
This study aims to identify the capital, habitus, and domain owned by Sunday school teachers in teaching Christian values ​​in Blitar City Church. Using a qualitative approach and Pierre Bourdieu's Habitus theory, data were collected through observation and interviews with Sunday school teachers in two research locations. The results of the study show that capital, domain, and habitus greatly influence the effectiveness of teaching Christian character. Differences in traditional and modern methods and communication patterns show a variety of approaches influenced by the context of each location.